Performance Study of Broadband and a Dual-Band Antenna- Array of Telecommunication Systems - Takialddin, al smadi (Anbar Journal of Engineering Sciences, 2022)
The antenna is a Modified Broadband Butterfly Antenna (MBBA). The technical parameters of such systems are heavily influenced by the qualities of the antenna feed devices. The aperture theory of antennas uses the representation of the radiation field of the antenna as a superposition of the fields of elementary sources, characterized by their type and amplitude-phase spatial distribution. The radiation field of an antenna of finite dimensions is a superposition of inhomogeneous spherical waves emitted by the antenna elements. This paper is primarily the study process, Radiation models were calculated using the model of the cavity plates, Simple Green model, and the strict commercial Electromagnetic Simulator. The modified active rectangular patches with the Gann diode were combined into arrays of E and H plane. Calculated and measured results for these two active arrays the beam scanning, the possibilities have been demonstrated for both arrays. The results of an electrodynamics numerical simulation were obtained. Broadband and multiband radio systems have already found widespread practical applications by utilizing basic antenna parameters and characteristics.